Hyperluminous starburst gives up its secrets. Issue 1 (8th August 2019) - Ivison, R J; Page, M J; Cirasuolo, M; Harrison, C M; Mainieri, V; Arumugam, V; Dudzevičiūtė, U
Abstract: HATLAS J084933.4 + 021443 was identified as a dusty starburst via its rest-frame far-infrared (far-IR) emission. Multifrequency imaging and spectroscopy revealed a cluster of four dusty galaxies at z  = 2.41, covering 80 kpc. Here, we use Atacama Large Millimetre Array to confirm a more distant, fifth protocluster member, and present X-ray and rest-frame optical imaging spectroscopy of the brightest, an unlensed hyperluminous IR galaxy (HyLIRG). The data reveal broad Hα and bright [N ii ] lines, and bright X-ray emission, characteristics that betray a Type-1 active galactic nucleus (AGN), strengthening evidence that AGN are ubiquitous amongst HyLIRGs. The accreting black hole is supermassive, M bh ≈ 2 × 10 9  M⊙, with little intrinsic absorption, N H ≈ 5 × 10 21  cm −2 . The X-ray properties suggest the accretion luminosity rivals that of the starburst, yet it is not obvious where this emerges in its panchromatic spectral energy distribution. We outline three scenarios that could give rise to the observed characteristics, and how we might distinguish between them. In the first, we see the AGN through the host galaxy because of the cavity it excavates. In the others, the AGN is not cospatial with the starburst, having been ejected via asymmetric gravitational radiation, or having evolved towards the naked quasar phase in an unseen companion.